Enhancing German language learning through interactive tools - Yuliya M. Kazhan; Valentyna A. Karpiuk (Academy of Cognitive and Natural Sciences, 2024)
This article explores the utilization of interactive tools in the creation of interactive exercises for German language lessons and the assessment of learners' performance. The concept of didacticization, which involves adapting educational materials and authentic texts, is examined in detail. The article outlines the essential steps for didacticizing authentic texts and provides examples of how digital tools can be employed to accomplish this task, thereby facilitating their integration into the educational process. The primary objectives of employing these tools are to foster language competence development and evaluate the attainment of learning outcomes. The study establishes that the utilization of mobile applications and Web 2.0 interactive tools effectively organizes students' work both within and outside the classroom, leading to the enhancement and refinement of their language competence.